1990
DOI: 10.1002/cm.970160207
|View full text |Cite
|
Sign up to set email alerts
|

The cytoskeletal system of mammalian primitive erythrocytes: Studies in developing marsupials

Abstract: Seeking to resolve conflicting literature on cytoskeletal structure in mammalian "primitive" generation erythrocytes, we have utilized the circulating blood of developing marsupials. In young of the Tammar Wallaby (Macropus eugenii) and the Gray Short-tailed Opossum (Monodelphis domestica), relatively large, nucleated primitive erythrocytes constituted nearly 100% of the circulating population at birth (= day 0) and in fetuses (Tammar) several days before birth. These cells were discoidal or elliptical, and fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 39 publications
(11 reference statements)
0
8
0
Order By: Relevance
“…In contrast, definitive erythrocytes of almost all mammals, with the exception of the immature red cells of camels, 42 lack these structural features. Although marginal bands have been detected in the primitive red cells of marsupials, 23 it is not clear whether true circumferential marginal bands exist in the primitive erythroblasts of mice. 43,44 Consistent with their enucleation, murine primitive erythroblasts lose intermediate filaments during their maturation in the bloodstream.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, definitive erythrocytes of almost all mammals, with the exception of the immature red cells of camels, 42 lack these structural features. Although marginal bands have been detected in the primitive red cells of marsupials, 23 it is not clear whether true circumferential marginal bands exist in the primitive erythroblasts of mice. 43,44 Consistent with their enucleation, murine primitive erythroblasts lose intermediate filaments during their maturation in the bloodstream.…”
Section: Discussionmentioning
confidence: 99%
“…14 Furthermore, large enucleated red cells have been noted in the bloodstream of mouse embryos by several investigators, 14,[18][19][20] raising the possibility that primitive erythroblasts might ultimately enucleate. Studies in the Syrian hamster and in marsupials indicate that primitive erythroblasts can enucleate, [21][22][23] To determine whether primitive erythroblasts enucleate in the mouse embryo and to examine the transition from primitive to definitive erythropoiesis, we raised antibodies to embryonic ␤H1-globin and optimized the immunohistochemical identification of primitive (␤H1-globin-positive) red cells. We report here that, contrary to widely held opinion, murine primitive erythroblasts enucleate and continue to circulate throughout late gestation and even into the postnatal period.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the erythrocyte membrane in vertebrates (except mammals) is reinforced by a bundle of microtubules, termed the marginal band, which circumscribes the cortical membrane in the horizontal plane of the cell. The marginal band is thought to provide structural support for the cell membrane and the elliptical cell morphology typical of vertebrate erythrocytes [2,3]. Electron microscopy studies indicated that human erythrocytes contain neither microtubules nor marginal band [4].…”
Section: Introductionmentioning
confidence: 99%
“…Electron microscopy studies indicated that human erythrocytes contain neither microtubules nor marginal band [4]. In view of this finding, further studies on tubulins of human erythrocytes were not performed, and many researchers presumed that they do not exist [2,3,5]. However, recent proteomics studies [6] showed the presence of various isoforms of tubulin in human erythrocytes.…”
Section: Introductionmentioning
confidence: 99%
“…The ICM is similar to the yolk sac hematopoietic tissue of higher vertebrates, since many hematopoietic transcription factors, including GATA-1 and GATA-2, are expressed in both the ICM of teleosts and the yolk sac of higher vertebrates (Detrich et al, 1995). The embryonic blood cells in teleosts are nucleated as are those in mammals, whereas the adult erythrocytes of teleosts are also nucleated, unlike the anucleated erythrocytes in mammals (Cohen et al, 1990).…”
Section: Introductionmentioning
confidence: 96%